Evidence of constant diversification punctuated by a mass extinction in the African cycads. Issue 1 (11th December 2013) - Yessoufou, Kowiyou; Bamigboye, Samuel O.; Daru, Barnabas H.; van der, Michelle
Abstract The recent evidence that extant cycads are not living fossils triggered a renewed search for a better understanding of their evolutionary history. In this study, we investigated the evolutionary diversification history of the genus Encephalartos, a monophyletic cycad endemic to Africa. We found an antisigmoidal pattern with a plateau and punctual explosive radiation. This pattern is typical of a constant radiation with mass extinction. The rate shift that we found may therefore be a result of a rapid recolonization of niches that have been emptied owing to mass extinction. Because the explosive radiation occurred during the transition Pliocene–Pleistocene, we argued that the processes might have been climatically mediated.